Differences in effectiveness of guava leaf extract (Psidium guajava linn) and lime water (Citrus aurantifolia) as irrigation material of root canal as inhibitors of bacteria Enterococcus faecalis (Laboratory of Microbiology Faculty of Pharmacy University - Syamsiah Syam; Nur F. Arifin; Nurkhairah Y. Irkan (Journal of Dentomaxillofacial Science, 2018)
Objective: Analyze the differences in inhibition zone diameter between 60% guava leaf extract (Psidium guajava linn.) and 100% lime juice (Citrus aurantifolia) when inhibiting the growth of Enterococcus faecalis bacteria.Material and Methods: This study was a laboratory experimental method with post-test only control group design. Sampling with purposive sampling using 4 treatments and 5 repetitions. Statistical test used One-way ANOVA.Results: The results of this study showed 60% guava leaf extract (Psidium guajava linn.) inhibited the growth of Enterococcus faecalis bacteria with a diameter of inhibition zone of 11.75 Â± 0.680 while 100% lime juice (Citrus aurantifolia) had a a diameter of inhibition zone of 20.67 Â± 2.655 mm, and based on statistical test determined p = 0.0046 < p = 0.05.Conclusion: The alternative hypothesis of this study was accepted and the results of this study indicate that there was a difference of effectiveness between 60% guava leaf extract (Psidium guajava linn.) and 100% lime juice (Citrus aurantifolia) extract as root canal irrigation material that can inhibit bacterial growth of Enterococcus faecalis.